THE EFFECT OF TEAMS ACHIEVEMENT DIVISION METHOD ON KNOWLEDGE AND ATTITUDE TO PREVENT SMOKING CESSATION AMONG ELEMENTARY SCHOOL CHILDREN IN KUPANG CITY, INDONESIA - riny pujiyanti; Budi Utomo; Padoli Padoli (Alta Dharma Publisher, 2019)
Keywords: student teams achievement, knowledge, attitude, smoking prevention, elementary school children